Short-term outcomes of open versus laparoscopic surgery in patients with metachronous colorectal cancer - Jiyun Li; Ruoxi Tian; Hengchang Liu; Haipeng Chen; Zhaoxu Zheng (BMC Surgery)
Abstract Background Few studies have assessed the safety and efficacy of laparoscopic surgery in patients with metachronous colorectal cancer (MCRC). This study aims to evaluate the safety and outcomes of laparoscopic surgery in MCRC patients who have previously undergone colorectal cancer surgery. Methods We compared the short-term outcomes of open versus laparoscopic surgery in patients with MCRC between October 2007 and October 2022. Results Among the 59 MCRC patients, 25 underwent laparoscopic surgery, whereas 34 received open surgery. The proportion of patients who underwent prior open surgeries was significantly greater in the open group than in the laparoscopic group (91.2% vs. 24.0%, p < 0.001). Three patients (12.0%) in the laparoscopic group required conversion to laparotomy due to severe intra-abdominal adhesions, all of whom had a history of open surgery for colorectal cancer. Compared to the open surgery group, the laparoscopic group presented significantly less estimated blood loss (56.80 ± 115.47 vs. 136.47 ± 158.61 ml, p = 0.038), a shorter time to the first flatus (2.20 ± 0.76 vs. 3.50 ± 0.62 days, p < 0.001), a shorter time to the first stool (2.92 ± 0.64 vs. 4.32 ± 0.64 days, p < 0.001), and a shorter postoperative hospitalization duration (7.24 ± 2.42 vs. 10.79 ± 3.50 days, p < 0.001). Conclusion Laparoscopic surgery for MCRC patients is a safe and less invasive alternative to open surgery, resulting in reduced estimated blood loss, faster recovery of bowel function, and shorter postoperative hospitalization.